Immobilization of uricase onto graphene oxide - Sidek, Nur Amirah (2015)
Immobilization of uricase onto graphene oxide was done by using two different methods, physical adsorption and also chemical modification of the surface of graphene oxide by using N’-(3-(dimethylamino)propyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) as cross-linkers. Graphene oxide is proved to be an excellent carrier for uricase immobilization due to it having a large surface area and abundant functional groups. The enzyme immobilization on graphene oxide can be done readily without using any cross-linking reagents or other additional surface modification. It can also be done by modifying the surface of graphene oxide for an enhanced performance. In this study, apart from using different methods, other paramaters such as the concentration of graphene oxide and also enzyme unit used are also varied to determine the best conditions for an optimum performance of the immobilized enzyme. The results obtained indicate that the immobilized enzyme perform better by using the chemical modification method, and the best parameters of uricase immobilization by this method were found as 1 mg/mL graphene oxide concentration and 1 u/ml uricase.